La Bible et l’inspiration littéraire dans les Suspiria de Profundis de T. De Quincey - Frédéric Slaby (Revue LISA)
As a consequence of his educational background, his religious experience and his literary influences, contacts between De Quincey and the Scriptures were recurrent throughout his life and works. His relationship with the Bible may be direct sometimes, but in Suspiria de Profundis is usually the result of a mediation through the works of Wordsworth, Milton and Bunyan. This article will thus examine another mediation in De Quincey’s Suspiria, namely the mediation of “power” which recurs in the biblical and literary references and on which De Quincey drew extensively.